How to Gain Meaningful Insights from People Analytics - Sushma Bhalkikar (New Delhi HR Information Services, 2021)
As John Scully has said, The future belongs to those who see possibilities before they become obvious, People analytics helps organisations see those possibilities.
Keywords: People Analytics